Case Report: From IgA nephropathy to pneumonia, periappendiceal abscess, pulmonary arterial hypertension, and basal ganglia calcification: a case of chronic active Epstein-Barr infection in a child - Fan, Shuying; Wang, Xin; Wei, Ning; Zhou, Qiumei; Wang, Wenhong (Frontiers in Pediatrics, 2025)
Chronic active Epstein–Barr virus infection (CAEBV) is a lymphoproliferative disorder characterized by persistent EBV infection, which can lead to multi-organ involvement. This case describes a child with CAEBV who initially presented with IgA nephropathy (IgAN) without characteristic infectious mononucleosis (IM) features. The patient initially presented with intermittent gross hematuria, Renal biopsy confirmed focal proliferative IgAN, and the child was treated with methylprednisolone pulse therapy followed by oral prednisone. During follow-up, the patient sequentially developed pneumonia caused by co-infection with EBV and Staphylococcus aureus, periappendiceal abscess, pancytopenia, Intermittently elevated peripheral blood EBV-DNA load, raising suspicion of CAEBV. Further investigations revealed the following findings: echocardiography demonstrated pulmonary arterial hypertension (PAH); cranial CT showed multiple bilateral basal ganglia calcifications; bone marrow biopsy detected EBV-DNA positivity (6.5 × 10³ copies/ml); renal tissue immunohistochemistry showed CD8+ cells (scattered, −50/HPF) and CD4+ cells (focal, −40/HPF), with negative LMP-1 but scattered EBER+ signals (−25/HPF). Based on persistently elevated peripheral blood EBV-DNA load, EBER-positive lymphocyte infiltration in renal tissue, evidence of multi-organ involvement, the diagnosis of CAEBV was established.